2021
DOI: 10.1186/s13000-020-01064-1
|View full text |Cite
|
Sign up to set email alerts
|

An “expressionistic” look at serrated precancerous colorectal lesions

Abstract: Background Approximately 60% of colorectal cancer (CRC) precursor lesions are the genuinely-dysplastic conventional adenomas (cADNs). The others include hyperplastic polyps (HPs), sessile serrated lesions (SSL), and traditional serrated adenomas (TSAs), subtypes of a class of lesions collectively referred to as “serrated.” Endoscopic and histologic differentiation between cADNs and serrated lesions, and between serrated lesion subtypes can be difficult. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…We presume that a lot of serrated lesions in the first years of the database were not properly detected by the endoscopists and, if resected, were misclassified as hyperplastic polyps by the pathologist. Secondly, SSLs that have extensive cytologic dysplasia might be difficult to differentiate from conventional adenomas (32). Finally, hyperplastic polyps in our study were as mentioned not included in the pathology register.…”
Section: Discussionmentioning
confidence: 93%
“…We presume that a lot of serrated lesions in the first years of the database were not properly detected by the endoscopists and, if resected, were misclassified as hyperplastic polyps by the pathologist. Secondly, SSLs that have extensive cytologic dysplasia might be difficult to differentiate from conventional adenomas (32). Finally, hyperplastic polyps in our study were as mentioned not included in the pathology register.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, by analysing the marker gene expression and functional pathways of these ‘HPV‐related clusters,’ we discovered that clusters 1 and 3 enriched in the normal cervix featured antineoplastic effects and highly expressed multiple tumour suppressors (SLC5A8, DERL3) (Figure 2D ), thereby suppressing cell proliferative, migratory and invasive capacities. 9 , 10 On the other hand, cluster 2, representing HSIL, manifested high cellular motor capacity, specifically expressing genes related to cell adhesion (CDH16, CDH17 and VSIG1) 11 , 12 and extracellular matrix degradation (CTSE) (Figure 2E ), thus potentially promoting the expansion of atypical cells in intraepithelial neoplasia progression. Additionally, we observed that clusters 6, 7, 9 and 13 (CASP14, PRSS27, CALML5) (Figure 2F ), which were enriched in CC, manifested high expression levels of genes related to carcinogenic pathways such as epithelial‐to‐mesenchymal transition, tumour cell proliferation, migration, invasion and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicated that the protective mechanism would be activated accordingly after HPV infection. The precancerous lesion of CC, the ‘HPV‐related HSIL cluster,’ highly expressed VSIG1, which is also a biomarker of colorectal cancer precursor lesions 12 . Therefore, we hypothesized that VSIG1 might be a critical molecule in precancerous epithelial lesions, which is worth further experimental investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, VSIG1 seemed to be upregulated in a variety of nongastric carcinomas ( 30 , 44 , 46 , 47 ). It was identified as a signature gene for gastric-type differentiation of serrated pathway-associated colon carcinoma ( 47 49 ) and lung adenocarcinoma ( 50 ). The coexpression of VSIG1 in the cytoplasm of hepatocytes with thyroid transcription factor 1 (TTF1) was also considered to be a potential lineage shift indicator of conventional to gastric-type hepatocellular carcinoma (HCC) ( 51 ).…”
Section: Vsig1mentioning
confidence: 99%